Ovrednotenje asociacij s cistoziro v naravnem rezervatu Strunjan z uporabo ribje favne kot indikatorske skupine - Orlando-Bonaca, Martina (Varstvo narave, 2008)
In the association with Cystoseira in the Strunjan Nature Reserva, the authors studied the coastal fish assemblage with parallel transects, a non-destructive SCUBA visual technique...
Keywords: vegetacija; flora; morje; sea; Jadransko morje; Adriatic Sea; cistozira; ribe; ribje populacije; biodiverziteta; environmental protection; varstvo narave; Tržaški zaliv; Gulf of Trieste